Jack’s Multiple Personality in Marrowbone Film - Prafitri, Wilma; Rahayu, Famala Eka Sanhadi; Ary Ivanka (General English Education, 2024)
This study examined the manifestation of Jack's multiple personality in the film Marrowbone. The film "Marrowbone," directed by Sergio G. Sanchez, serves as the primary source for this theory. The narrative revolves around a nuclear family including four siblings: Jack Marrowbone, the eldest, followed by Jane Marrowbone, Billy Marrowbone, and Sam Marrowbone. Due to enduring psychological distress caused by their biological father, they are compelled to return to their mother's ancestral residence. The trauma induced depression in Jack and triggered the manifestation of his multiple personality. The objective of this thesis is to examine the primary factors contributing to Jack's manifestation of multiple personality disorder. The data for this thesis was gathered by qualitative methods, namely by analyzing screenplays, dialogue, and scenes from films. The researcher analyzed the data using Haddock as theoretical framework. The findings indicate that Jack possesses three additional personalities, which correspond to those of his deceased younger siblings. The findings of this research indicate that negative previous experiences can have a detrimental impact on an individual's psychological well-being. By analyzing the personality, background, and history of individuals who suffer from this disorder, the audience can gain insight into the factors contributing to its manifestation.